Using Short Stories to Enhance Grammar Learning in ELT Classrooms: : A Comprehensive Literature Review - Nurhayati, Nurhayati; Sedubun, Stenlly (DIDASCO, 2024)
This study aims to investigate the effectiveness of using short stories as a tool to enhance grammar learning in English Language Teaching (ELT) classrooms. The design of this present study is a literature review design: A systematic review of relevant literature was conducted to identify studies that examined the use of short stories in the context of grammar instruction in ELT classrooms. The findings of this literature review indicate that the use of short stories in ELT classrooms can effectively enhance grammar learning. Short stories provide meaningful contexts for grammar instruction, engage students in authentic language use, and promote active participation and interaction. Moreover, short stories can foster students' motivation, creativity, critical thinking, and cultural awareness. There is a high recommendation for practical implications for teachers and curriculum designers, emphasizing the need for appropriate selection, adaptation, and implementation of short stories to maximize their potential in enhancing grammar learning in ELT classrooms. Keywords— Short stories, Grammar Learning, ELT Classrooms